Effect of Irrigation with Diluted Winery Wastewater on the Performance of Two Grass Cover Crops in Vineyards - Fourie, J.C.; Theron, H.; Ochse, C.H. (South African Journal of Enology and Viticulture, 2016)
Pennisetum glaucum L. cv. Babala (pearl millet) established as a summer catch crop followed by Avena sativa L. cv Palinup (oats) established as a winter catch crop were irrigated with winery wastewater diluted to eight chemical oxygen demand (COD) levels ranging between 100 mg/L and 3 000 mg/L. The diluted wastewater treatments were compared to irrigation with river water. The dry matter production (DMP) of oats, if not preceded by pearl millet, tended to improve when irrigated with winery wastewater. Growth of pearl millet peaked during the period when 91% of the diluted winery wastewater was applied. Winery wastewater improved the DMP of pearl millet. No trends were observed in the nutrient levels of the above-ground growth of the two interception crops. However, Na levels increased over time. Using both species, too high levels of macro-nutrients were intercepted, but insignificant amounts of Na were removed. Irrigation with winery wastewater with COD levels between 1 500 mg/L and 2 500 mg/L may be sustainable if only pearl millet is employed as an interception crop. Fertiliser needed to maintain the nutrient balance in the soil resulted in an additional cost of approximately R2 800/ha/yr. However, the fodder may provide an income in excess of R15 000/ha/yr.